Modelling and Characterization of Subcarrier Intensity Modulation Based Free Space Optical Communication - Jayakrishnan, U. S.; A. Prabin (Asian Journal of Electrical Sciences, 2014)
This paper is an investigation to model and characterize subcarrier intensity modulation employing M-ary phase shift keying and rectangular quadrature amplitude modulation for optical wireless communication over different turbulence channels. Atmospheric turbulence results in many effects causing fluctuation in the received optical power .The popular models for describing atmospheric turbulence are the lognormal distribution (for weak turbulence induced irradiance fluctuation), the K- distribution (for strong turbulence induced irradiance fluctuation), the negative exponential distribution (for irradiance fluctuation in saturated turbulence conditions), and the Gamma-Gamma distribution (for describing irradiance fluctuation over a wide range of turbulence regimes from weak to strong turbulence). The adaptive schemes offer efficient utilization of optical wireless communication channel capacity by adapting the modulation order according to the received signal-to-noise ratio and a pre-defined target bit-error rate requirement. The improved spectral efficiency can be achieved by the adaptive systems without increasing the transmitter power.